The Role of Transformational Leadership and Psychological Empowerment Toward Employee Creativity - Alshawabkeh, Ibrahim; Ahmad, Nursaadatun Nisak; Rashid, Ana Haziqah A; Panatik, Siti Aisyah; Al-Rusa, Adolf; Liyana, Aina (Advances in Social Sciences Research Journal, 2024)
Employee creativity is a fundamental cognitive skill; according to the latest statistics, employee creativity is the most crucial factor for future success and is integrated into the bottom line in all organisations. Previous research reported a significant relationship between transformational leadership and employee creativity; however, the mechanism of this relationship is still unfolding, and the mediatory role of these variables is largely unexplored. Thus, this study aims to examine the mediating effect of psychological empowerment between transformational leadership and employee creativity within Malaysia’s customer service industry due to its crucial role in meeting changing demands through excellent service in a socio-cultural context. A total of 429 responses were collected through questionnaires consist of four main parts including demographic information, transformational leadership, employee creativity and psychological empowerment. The data were analysed using measurement and structural models through smart-PLS using structural equation modelling with bootstrapping. The findings revealed that transformational leadership does not have a significant positive relationship with employee creativity. Meanwhile, the result demonstrates that there is a significant relationship between transformational leadership and psychological empowerment as well as between psychological empowerment and employee creativity. Interestingly, the findings revealed that psychological empowerment mediates the relationship between transformational leadership and employee creativity. This study contributes to the theoretical perspective in terms of the mediating role of psychological empowerment in the relationship between transformational leadership and employee creativity. As for the practical implications, this study provides empirical evidence for the organisation to design interventions that enhance creativity by empowering psychology among the employees.